Інтродукція регіональних видів роду Allium L. у Криворізький ботанічний сад - Kucherevskyi, V.V.; Schol, H.N. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Data about spreading of Allium L. genus species in Right-Bank Steppe Prydniprov'y natural ecotopes are cited and their sozological status is presented. The assessment of success of regional species of genus Allium introduction into Kryvyi Rih Botanic Garden is given.